Roles of FGFs As Paracrine or Endocrine Signals in Liver Development, Health, and Disease - Itoh, Nobuyuki; Nakayama, Yoshiaki; Konishi, Morichika (Frontiers in Cell and Developmental Biology, 2016)
The liver plays important roles in multiple processes including metabolism, the immune system, and detoxification and also has a unique capacity for regeneration. FGFs are growth factors that have diverse functions in development, health, and disease. The FGF family now comprises 22 members. Several FGFs have been shown to play roles as paracrine signals in liver development, health, and disease. FGF8 and FGF10 are involved in embryonic liver development, FGF7 and FGF9 in repair in response to liver injury, and FGF5, FGF8, FGF9, FGF17, and FGF18 in the development and progression of hepatocellular carcinoma. In contrast, FGF15/19 and FGF21 are endocrine signals. FGF15/19, which is produced in the ileum, is a negative regulator of bile acid metabolism and a stimulator of gallbladder filling. FGF15/19 is a postprandial, insulin-independent activator of hepatic protein and glycogen synthesis. It is also required for hepatocellular carcinoma and liver regeneration. FGF21 is a hepatokine produced in the liver. FGF21 regulates glucose and lipid metabolism in white adipose tissue. Serum FGF21 levels are elevated in non-alcoholic fatty liver. FGF21 also protects against non-alcoholic fatty liver. These findings provide new insights into roles of FGFs in the liver and potential therapeutic strategies for hepatic disorders.